YOUNG LEARNERS’ RESPONSES ON THE USE OF ANIMATION IN AN ENGLISH CLASS - Ruruh Mindari; M.J. Kriesye Sriemulyaningsih; Andrew Joewono (Magister Scientiae, 2019)
In an attempt to arouse young learners’ interest and active participations in learning English in this digital era, a prototype of speaking material for primary school students has been developed. The material developed is a computer-based interactive module for primary school students. Designed in the form of animation featuring animal characters, the themes were presented in dialogues as well as brief introductory narrations whereas the speaking activities were designed based on language chunks accompanied with pronunciation practice. To find out young learners’ reactions on the use of the materials developed, some try outs were conducted in some English classes of young learners. From the try outs it was found out that the young learners’ responses varied. Some seemed interested but shy to participate, some participated with encouragements, and some others participated actively without encouragements. However, the overall perceptions of the young learners on the use of the digital materials showed their interest and enthusiasm. In terms of the quality of the materials, some aspects that needed improvements were the age of the voice actors, the operational buttons, and the variations of the interactive activities.